2012
DOI: 10.1371/journal.pone.0044222
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Periosteal and Endocortical Responses to Axial Tibial Compression Loading in Conditional Connexin43 Deficient Mice

Abstract: The gap junction protein, connexin43 (Cx43) is involved in mechanotransduction in bone. Recent studies using in vivo models of conditional Cx43 gene (Gja1) deletion in the osteogenic linage have generated inconsistent results, with Gja1 ablation resulting in either attenuated or enhanced response to mechanical load, depending upon the skeletal site examined or the type of load applied. To gain further insights on Cx43 and mechanotransduction, we examined bone formation response at both endocortical and periost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 35 publications
8
95
1
Order By: Relevance
“…Hence, Cx43 has been thought to be requisite for sensing mechanical loads. However, interestingly, some recent studies have shown that deletion of Cx43 in osteocytes increased bone mass in response to mechanical loads [134,135]. These experimental results contradict those of previous studies, indicating that the role of Cx43 in osteocytes under loaded conditions must be further elucidated.…”
Section: Mechanosensation In Osteocytesmentioning
confidence: 73%
“…Hence, Cx43 has been thought to be requisite for sensing mechanical loads. However, interestingly, some recent studies have shown that deletion of Cx43 in osteocytes increased bone mass in response to mechanical loads [134,135]. These experimental results contradict those of previous studies, indicating that the role of Cx43 in osteocytes under loaded conditions must be further elucidated.…”
Section: Mechanosensation In Osteocytesmentioning
confidence: 73%
“…Many gene knockout studies have demonstrated differential phenotypes in cortical and cancellous bone; some notable examples are the primary effect in cancellous bone of absence of estrogen receptor alpha in bone cells [51-55], the previously mentioned cortical phenotype in mice lacking Wnt16 [33, 34], and the decrease in cortical but not cancellous bone volume when BMP2 is deleted from early-stage osteoblasts [56]. With in vivo compression of the mouse tibia, cancellous bone is often more responsive to mechanical loading than cortical bone [21, 57]; however, gene knockouts can modify this responsiveness in a site-specific manner [55, 58]. Future studies utilizing our methods to determine the baseline transcription and response to loading in cortical and cancellous bone in genetically modified mice will help unravel the complex molecular mechanisms responsible for in vivo bone homeostasis and mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the regulation of the RANKL/OPG ratio, as detailed above, several groups have shown that collagen processing, and specifically collagen cross-linking by lysyl oxidase ( Lox ), is abnormal in osteoblast Gja1 cKO mice [13, 28], leading to disorganized fibrillar collagen, hypomineralized bone matrix and decreased bone strength; these abnormalities are particularly severe in cKO Tw2 mice, where Cx43 is absent in the entire chondro-osteogenic lineage [13]. As already noted, diminished sclerostin expression, a key regulator of bone homeostasis, may explain the enhanced osteo-progenitor proliferation and exuberant periosteal apposition observed Cx43 cKO knockouts [13, 32, 38, 39]. Therefore, Cx43 is a positive regulator of sclerostin, although this action is most likely indirect [32], as a consequence of either increased osteocyte viability [32], or stimulation of osteoblast differentiation [13].…”
Section: Cx43 In Skeletal Development and Homeostasismentioning
confidence: 99%
“…While in an early study from our group a 3-point bending protocol resulted in reduced bone endocortical bone formation in cKO Col1A1 mice [44], an opposite effect has been consistently reporter later at the periosteal surface. Using either cantilever bending of the tibia in cKO OG2 mice – in which Gja1 is ablated by OG2-Cre in mature osteoblasts and osteocytes – [29], or axial tibial compression in cKO Tw2 mice [38], or ulna compression in cKO Dmp1 mice [45], to apply mechanical load, a consistent enhancement of periosteal bone formation response has been reported in Cx43-deficient mice relative to wild type mice, even though with some slight differences among the different experimental settings. Thus, lack of Cx43 increases the sensitivity of periosteal bone formation to mechanical load.…”
Section: Cx43 In Adaptive Responses To Skeletal Stimulimentioning
confidence: 99%